STUDI TENTANG AMIL ZAKAT (Mazahib, 2007)
Amil zakat is the collector of zakat (obligated Islamic charity) from the zakat payers and the distributors of zakat to the beneficiaries assigned by the government. This concept come from the tradition of the prophet and the practices of caliph. As the collector of zakat, amil zakat is entitled to get 1/8 from the collected zakat fund. Others say that amil zakat is entitled to a salary, and this can be issued from the collected zakat or from the Islamic treasury.